What Parameters Influence the Effect of Cold-Water Immersion on Muscle Soreness? An Updated Systematic Review and Meta-Analysis - Batista, Natanael P. [UNESP] (2023)
Objective: Our objective was to determine the efficacy of cold-water immersion (CWI) on the management of muscle soreness to identify the impact of immersion time, water temperature, CWI protocol, and type of exercise on this outcome. Design: Intervention systematic review and meta-analysis. Setting: MEDLINE/PubMed, Embase, Central, and SPORTDiscus databases were searched from their earliest record to July 30, 2020. Only randomized controlled trials that assessed muscle soreness comparing CWI and control were included. Studies were pooled in different subgroups regarding the used protocol: water temperature (severe or moderate cold), immersion time (short, medium, or longer time), CWI protocol (intermittent or continuous application), and type of exercise (endurance or resistance exercise). Data were pooled in a meta-analysis and described as weighted mean difference (95% confidence interval, P, 0.05). Participants: Athletes and nonathletes. Interventions: Cold-water immersion and control condition. Main Outcome Measures: Muscle soreness. Results: Forty-four studies were included. For immediate effects, CWI was superior to control regardless of water temperature and protocol, and for short and medium immersion times and endurance exercises. For delayed effects, CWI was superior to control in all subgroups except longer immersions time. Conclusions: This study suggests that CWI is better than control for the management of muscle soreness and water temperature and CWI protocol do not influence this result, but only short and medium immersions times presented positive effects. Aiming immediate effects, the best results suggest CWI application only after endurance exercises, while delayed effect CWI was superior both after endurance and resistance exercises.